Exploring the 2′-Hydroxy-Chalcone Framework for the Development of Dual Antioxidant and Soybean Lipoxygenase Inhibitory Agents - Ioanna Kostopoulou; Andromachi Tzani; Nestor-Ioannis Polyzos; Maria-Anna Karadendrou; Eftichia Kritsi; Eleni Pontiki; Thalia Liargkova; Dimitra Hadjipavlou-Litina; Panagiotis Zoumpoulakis; Anastasia Detsi (Molecules, 2021)
2′-hydroxy-chalcones are naturally occurring compounds with a wide array of bioactivity. In an effort to delineate the structural features that favor antioxidant and lipoxygenase (LOX) inhibitory activity, the design, synthesis, and bioactivity profile of a series of 2′-hydroxy-chalcones bearing diverse substituents on rings A and B, are presented. Among all the synthesized derivatives, chalcone 4b, bearing two hydroxyl substituents on ring B, was found to possess the best combined activity (82.4% DPPH radical scavenging ability, 82.3% inhibition of lipid peroxidation, and satisfactory LOX inhibition value (IC50 = 70 μM). Chalcone 3c, possessing a methoxymethylene substituent on ring A, and three methoxy groups on ring B, exhibited the most promising LOX inhibitory activity (IC50 = 45 μM). A combination of in silico techniques were utilized in an effort to explore the crucial binding characteristics of the most active compound 3c and its analogue 3b, to LOX. A common H-bond interaction pattern, orienting the hydroxyl and carbonyl groups of the aromatic ring A towards Asp768 and Asn128, respectively, was observed. Regarding the analogue 3c, the bulky (-OMOM) group does not seem to participate in a direct binding, but it induces an orientation capable to form H-bonds between the methoxy groups of the aromatic ring B with Trp130 and Gly247.